Enzyme Dehydration Using Microglassification™ Preserves the Protein's Structure and Function. Issue 2 (29th December 2014) - Aniket; Gaul, David A.; Bitterfield, Deborah L.; Su, Jonathan T.; Li, Victoria M.; Singh, Ishita; Morton, Jackson; Needham, David
<x xml:space="preserve">Abstract</x> Controlled enzyme dehydration using a new processing technique of Microglassification™ has been investigated. Aqueous solution microdroplets of lysozyme, α‐chymotrypsin, catalase, and horseradish peroxidase were dehydrated in n‐pentanol, n‐octanol, n‐decanol, triacetin, or butyl lactate, and changes in their structure and function were analyzed upon rehydration. Water solubility and microdroplet dissolution rate in each solvent decreased in the order: butyl lactate > n‐pentanol > triacetin > n‐octanol > n‐decanol. Enzymes Microglassified™ in n‐pentanol retained higher activity (93%–98%) than n‐octanol (78%–85%) or n‐decanol (75%–89%), whereas those Microglassified™ in triacetin (36%–75%) and butyl lactate (48%–79%) retained markedly lower activity. FTIR spectroscopy analyses showed α‐helix to β‐sheet transformation for all enzymes upon Microglassification™, reflecting a loss of bound water in the dried state; however, the enzymes reverted to native‐like conformation upon rehydration. Accelerated stressed‐storage tests using Microglassified™ lysozyme showed a significant (p < 0.01) decrease in enzymatic activity from 46, 560 ± 2736 to 31, 060 ± 4327 units/mg after 3 months of incubation; however, it was comparable to the activity of the lyophilized formulation throughout the test period. These results establish Microglassification™ as a viable technique for enzyme preservation without affecting its structure or function. © 2014 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 104:640–651, 2015